How the instantaneous net drag-force profile can quantify front-crawl and backstroke swimming technique: A practical perspective - Formosa, D. P. (Journal of Fitness Research, 2012)
The aim of this research was to use instantaneous net drag-force profiles to understand front-crawl and backstroke swimming technique. Twenty-nine elite front-crawl and 19 elite backstroke swimmers (FINA point ranking 924.5 ± 69.0) were recruited. From the net drag-force profile the Minimum and Maximum net force occurred during the insweep phase and during the upsweep phase of the front-crawl stroke, respectively. When swimming backstroke the minimum and maximum net drag-forces occurred during the pull phase and push stroke phases, respectively. When turning their head to breath the swimmers increased the net drag-force by 22%, which could be detrimental to swimming performance. When comparing the variables of swimming speed and the range of force fluctuations participants who exhibited smaller intra-stroke force changes produced faster swimming speeds. This practical knowledge can assist coach, sports scientist or exercise professional in providing stroke correction during swimming.